Patrimônio do cotidiano e turismo: andanças investigativas, afetivações e memórias no município de Rolândia, no estado do Paraná, Brasil. - Mancini, Lorena Angélica (My University, 2025)
The present research focus on Daily Heritage and Tourism: Investigative wanderings, memories and affectiveness on Rolândia city, in Paraná state, Brazil. As main goal, I hereby put forward the concept of Daily Heritage and its relation to Tourism, thought from investigative wanderings on Rolândia city, in the state of Parané, Brazil. The objectives aim specifically to: present the course of heritage build up, considering feelings, concepts and public politics; present the proposition of Daily Heritage, relating it to generation of affectiviness and memories; discuss the relation between Heritage and Tourism, considering the ecosystemic dimension and Reverse Tourism; present reports of investigative Wanderings on Rolândia city, in the state of Paraná, Brazil. In theoretical terms, the understanding about Tourism bonds to the complexity and procedures to touristic reckoning and doing, being oriented on proposition of Reverse Tourism according to Baptista (2021). A theoretical and conceptual recovery regarding Heritage and Routine is done, aiming the conceptual proposition of Daily Heritage. The study has been developed through complex ecosystemic philosophical theoretical-methodological of Contemporary Science, with holistic orientation, that also substantiate the wider studies of Amorcomtur!, Sutdy Group for Communication, Tourism, Lovingness and Autopoiesis, to wich it is bound. As methodological strategy, uses Knowledge Cartography and Rhizomatic Matrix (Baptista; Eme. 2023) known as complex, multimethodological and procedural. For investigative practice, it laid on the concept of Com-versations Places and Subjects (Baptista, 2020c), transversal action that outlines the verbal and characterizes as loving, procedural and relational. Operationally, the research has been oriented on Sentimental Cartography (Rolnik, 1989), holding the Wanderings as methodological device, according Baptista?s proposition, aiming to register the feelings and singularities of each space and the relation to the subjects. The proposition of Daily Heritage correspond to the search for conceptual expansion of heritage and the reckoning and diversity appreciation, and historically unseen groups. It constitutes itself on the importance of daily ordinary activities recognition, of the simplicity, the affectiveness and memories that bound the subjects to their living spaces. Explicits and proposes the rupture with monumental and sacred logic, and aims the (re)cognition and appreciation stem from the glance and signification of local residents, captured during and by means of investigative wanderings of the researcher. Through this perspective, the heritage has been observed under the perspective of daily routines. This heritage has been observed on wanderings, where it was possible to realize affectiveness generated on day-by-day life, on the relation between sibjects and places, building the memory of urban space. [resumo publicado pelo autor]
O presente estudo tem como foco central Patrimônio do Cotidiano e Turismo: andanças investigativas, afetivações e memórias no município de Rolândia, no estado do Paraná, Brasil. Como objetivo geral, busco propor o conceito de Patrimônio do Cotidiano e sua relação com o Turismo, considerada a partir de afetivações e memórias reconhecidas em andanças investigativas no município de Rolândia, no estado do Paraná, brasil. Especificamente, os objetivos são direcionados a: apresentar a trajetória de construção do patrimônio, considerando sentidos, conceitos e políticas públicas; apresentar a proposição Patrimônio do Cotidiano, relacionando-a com a produção/geração de afetivações e memórias; discutir a relação entre Patrimônio e Turismo, considerando a dimensão ecossistêmica e de Avesso do Turismo; apresentar relatos de Andanças investigativas no município de Rolândia, no estado do Paraná, Brasil. Nessa perspectiva, o elemento de análise considerado encontra-se no patrimônio tomado na perspectiva do cotidiano. Esse patrimônio é observado em andanças, onde foi possível perceber afetivações geradas na vida cotidiana, na relação dos sujeitos nos lugares e na relação entre sujeitos e lugares, constituindo a memória do espaço citadino. Em termos teóricos, a compreensão do Turismo vincula-se à complexidade e processualidade do saber e fazer turístico, tendo orientação na proposição do Turismo do Avesso, de Baptista (2021). É feita uma retomada teórico-conceitual a respeito de Patrimônio e Cotidiano, para chegar à proposição conceitual Patrimônio do Cotidiano. O estudo foi desenvolvido com orientação filosófico teórico-metodológica ecossistêmica complexa da Ciência Contemporânea, com orientação holística, que fundamenta também os estudos mais amplos do Amorcomtur! Grupo de Estudos em Comunicação, Turismo, Amorosidade e Autopoiese. Como estratégia metodológica, utiliza a Cartografia dos Saberes e as Matrizes Rizomáticas (Baptista, 2014) que se caracterizam por serem complexas, plurimetodológicos e processuais. Para a prática investigativa o estudo se apoiou no conceito de 'Com-versar' Lugares e Sujeitos (Baptista,2020c), ação transversal que que ultrapassa o verbal e se caracteriza como relacional, processual e amorosa. Operacionalmente a pesquisa teve orientação na Cartografia Sentimental da Cidade (Rolnik,1989), tendo como dispositivo metodológico as Andanças, conforme proposição de Baptista, que foram realizadas a fim de investigar as sensações e singularidades de cada espaço na relação que estabelecem com os sujeitos. A proposição do Patrimônio do Cotidiano se une a um contexto maior na busca pela ampliação conceitual do patrimônio e reconhecimento da diversidade e de grupos historicamente invisibilizados. Se constitui nas práticas ordinárias do cotidiano, no simples, nas afetivações e memórias que conectam os sujeitos aos seus espaços vividos. Tenciona um rompimento com a lógica monumental e sacralizada, e busca o (re) conhecimento e valorização a partir do olhar e significações do sujeito/morador. [resumo publicado pelo autor]
Keywords: Turismo - Rolândia (PR); Turismo - Usos e costumes; Patrimônio cultural; Política pública; Tourism - Rolândia (Brazil); Tourism - Social life and customs; Cultural property; Cultural property